Transmitted electron exposure in electron beam lithography for double-side patterning of bi-layer metasurfaces on a SiNx membrane - Jinyu Guo; Yifei Wang; Hao Quan; Shuoqiu Tian; Qiucheng Chen; Wentao Yuan; Qingxin Wu; Kangping Liu; Yifang Chen; Qiong He; Lei Zhou (Micro and Nano Engineering)
Metasheets, composed of two identical metasurfaces closely aligned to each other within a mode-coupling distance on the two opposite sides of a SiNx membrane, are of unique functionalities for effective modulation of electromagnetic waves by nanoscale metallic structures. Although the physical image is readily clear, nanofabrication of such a two-sided devices with identical patterns still remains a big challenge because of the e-beam spreading caused by forward scattering in both resists and membranes. In this work, an innovative transmitted electron beam lithography (TEBL) was developed for metasheets. Three different resist stacks were tried and compared to eliminate the pattern deviation between them. A simulation study of TEBL was systematically carried out to figure out a reliable process window for replicating identical Au-gratings on the two opposite sides. The principle behind the success of replicating two identical metasurfaces on opposite sides is analyzed. The developed TEBL in this work extends the application of electron beam lithography to double-sided patterning for novel optical devices such as metasheets.